Hemodynamic characterization of transient blood flow in right coronary arteries with varying curvature and side-branch bifurcation angles. (1st September 2015) - Liu, Guiying; Wu, Jianhuang; Ghista, Dhanjoo N.; Huang, Wenhua; Wong, Kelvin K.L.
Abstract: Hemodynamics plays a critical role in the development and progression of plaques that are prone to sites of arterial curvatures and branch bifurcations. The occurrence of atherosclerosis at curvatures of coronary arteries and at the bifurcation sites of their branches are of medical importance. In this study, we have employed computer simulation coupled with a parametric analysis to rigorously quantify the transient wall shear stress ( WSS ) and wall pressure gradient ( WPG ) in idealized and image-based right coronary artery (RCA) models with side-branches, in order to explore the effects of curvature and bifurcation on blood flow characteristics and its hemodynamic variables. Upon establishing and implementing this parametric analysis framework, it is found that the relatively lower wall shear stress and WPG regions at the curvature and branch bifurcation sites of arteries coincide with the plaques prone points of the three investigated image-based arteries, to thereby confirm the correlation of the fluid mechanical properties with the arterial geometry variation in consistence with the data from existing literatures. Moreover, the average WSS and Pressure drop (from inlet to outlet) are significantly increased with the more complex geometry of realistic arteries in comparison with idealized arterial models. It can hence be concluded that the geometry of curvature and angulation of the side branches has a significant effect on the WSS and WPG in hemodynamics analysis of RCAs and its correlation with atherosclerotic lesions.